Penilaian Kinerja Keuangan Perbankan Dengan Metode Camel (Studi Kasus Pada PT. Bank Rakyat Indonesia (Persero) Tbk dan PT. Bank Central Asia Tbk) - Muhammad Rizka Maulana Effendi; Hendra Sastrawinata (Jurnal Aplikasi Manajemen dan Bisnis, 2021)
This research was motivated by questions regarding the comparison of the financial performance of state-owned banks and the national private. In this study, the object of the case study was PT Bank Rakyat Indonesia (Persero), Tbk, owned by the Government which has an asset value of 1,017 trillion Rupiah, with PT Bank Central Asia, Tbk, owned by the National Private Company with an asset value of 783 trillion Rupiah. After calculating the overall results, both PT BCA Tbk Bank, and PT BRI (Persero) Tbk bank could be categorized as healthy banks, even though the LDR, NPL, ROE and BOPO values were from PT Bank Rakyat Indonesia (Persero), Tbk, greater than PT Bank Central Asia, Tbk, and the ROA and CAR values of PT BCA, Tbk were higher than that of PT Bank Rakyat Indonesia (Persero), Tbk.